2016
DOI: 10.1016/j.atmosenv.2016.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting vehicular emissions in high spatial resolution using pervasively measured transportation data and microscopic emissions model

Abstract: h i g h l i g h t sWe present a novel method for predicting air pollution emissions using transport data. Study uses measured microscopic transport data and a microscopic emissions model. GPS data from over 15,000 vehicles were analyzed to quantify speeds and accelerations. CO 2 , NO x , VOCs and PM were modeled in high spatio-temporal resolution. Highly localized areas of elevated emissions were identified. a b s t r a c t Air pollution related to traffic emissions pose an especially significant problem in ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 47 publications
0
56
0
Order By: Relevance
“…We further compare the proposed emission estimation method with two different methods: (a) one based on flow data from microwave detectors  and the static fleet information (provided by the Bureau of Statistics of Hangzhou), which is similar to the method proposed by Nyhan et al (2016); (b) the other one based on the flow data and uniform dynamic fleet composition, both observed by LPR cameras. As shown in Figure 11, method (a) tends to underestimate the total emissions during the daytime, which is understandable given that the static fleet information may not be an accurate and up-to-date representation of the vehicle fleet during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…We further compare the proposed emission estimation method with two different methods: (a) one based on flow data from microwave detectors  and the static fleet information (provided by the Bureau of Statistics of Hangzhou), which is similar to the method proposed by Nyhan et al (2016); (b) the other one based on the flow data and uniform dynamic fleet composition, both observed by LPR cameras. As shown in Figure 11, method (a) tends to underestimate the total emissions during the daytime, which is understandable given that the static fleet information may not be an accurate and up-to-date representation of the vehicle fleet during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…When work locations were considered in addition to residential, exposures to NOX and NO2 were found to increase by 5 -10 ppb (Shafran-Nathan et al, 2017). Nyhan et al (2016) found significant differences between dynamic and static population-weighted exposures in New York City using cellular data with spatiotemporal PM2.5 concentrations. It was found travelling to work locations, usually in urban areas with higher pollutant levels, contributed to this variation from home concentrations, particularly time spent in transport microenvironments contributed significantly to overall exposure (Dons et al, 2011;de Nazelle et al, 2013).…”
Section: Comparison To Other Studiesmentioning
confidence: 89%
“…In other studies assessing dynamic air pollution exposure, mobility or time-activity data were derived from transport and activity-based simulation models (Setton et al, 2011;Dhondt et al, 2012), GPS (Dons et al, 2011), mobile-based tracking (de Nazelle et al, 2013), travel smartcard (Smith et al, 2016), travel surveys (Saraswat et al, 2016) or cellular network information (Dewulf et al, 2016;Nyhan et al, 2016). These were combined with air pollution modeling to assess personal and population exposure to pollutants.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Gately et al, (2017), emissions are estimated by assimilating GPS data with speed and flow data derived from stationary detectors or a traffic model. Nyhan et al, (2016) use GPS trajectory data from taxis, available for a large urban area in Singapore, to estimate emissions. However, they conclude that Singapore is a special case, where taxi data can be used to infer general traffic pattern and the total volume, but this is not necessarily true for other urban areas.…”
Section: Approaches Based On Trajectory Datamentioning
confidence: 99%